Crawl or trudgen? A factorial structure of the two most important swimming styles in youth water polo players - Perazzetti, A.; Dopsaj, M.; Tessitore, A. (XIVth International Symposium on Biomechanics and Medicine in Swimming Proceedings, 2023)
INTRODUCTION: A strong performance in water polo requires a balance of several skills, including the ability to change the swimming style, as fast as possible, according to the game situations. To cope with horizontal phases, crawl and trudgen are the most required styles, which could be performed with the head above water, while leading the ball and while handling the ball1. The purpose of this study was to define the most important modality of these two swimming styles for the assessment of two youth water polo age (U14 and U16).